SELF-ORGANIZATION - A MEANS OF SELF-DEVELOPMENT OF PUPILS AND STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
In article, the author submits a philosophical, psychological substantiation and generalization of results of pedagogical experiment on introduction to educational practice of pedagogical system of self-organizing of pupils and students a yak of means of self-development of the person.
Keywords: self-organising; self-development; self-programming; acreative pedagogical psrsdigm